Menstrual Health Practices among Physically Disabled Women and Girls in Masaba North Sub-County, Nyamira County, Kenya - Josephine Orare; Mohamed Karama; Phitalis Were Masakhwe (Adventist University of Africa, 2023)
Background: Menstrual health is crucial for achieving Sustainable Development Goals (SDGs) and gender equality. Disabled women and girls may experience double prejudice during menstruation. This study aimed to establish menstrual health practices of physically disabled women and girls in Masaba North Sub-county, Nyamira County, Kenya. Methods: A cross-sectional study design was used. A census was conducted for all (111) registered physically disabled women and girls (15-49 years). A structured questionnaire was used to collect quantitative data through face-to-face interviews. Purposive sampling was used to select 12 physically disabled women and girls for Focus Group Discussions (FGDs), ten caregivers and four physically disabled women and girls for in-depth interviews, two Water, Sanitation, and Hygiene (WASH) experts, three public health officers, three representatives of persons with disabilities, and one policymaker for key informant interviews. Chi-Square test and binary logistic regression were used to test the association between menstrual health practices and the independent variables. OR, 95% CI, and p-value < 0.05 were considered statistically significant. Results: More than half (55%) of physically disabled women and girls had unsafe menstrual health practices. Maternal education level (OR 3.794, 95% CI 1.345-10.705) modified toilets (OR 2.937, 95% CI 1.135-7.602) and ability to shower and change in privacy (OR 2.845, 95% CI 1.211-6.683) were significantly associated with safe menstrual health practices. The qualitative study's themes included WASH services, awareness, experiences, and the unique needs of physically disabled women and girls. Conclusion: Mothers' education level, modified toilets, ability to shower, and change in privacy were independently associated with safe menstrual health practices.